2009
DOI: 10.1021/bc9003926
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluorophore Excimers and Exciplexes as FRET Donors in DNA

Abstract: We describe studies aimed at testing whether oligomeric exciplex-and excimer fluorophores conjugated to DNA have the potential to act as donors for energy transfer by the Förster mechanism. Oligodeoxyfluorosides (ODFs) are composed of stacked, electronically interacting fluorophores replacing the bases on a DNA scaffold. The monomer chromophores in the twenty tetramer-length ODFs studied here include pyrene (Y), benzopyrene (B), perylene (E), dimethylaminostilbene (D), and a nonfluorescent spacer (S); these ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 52 publications
2
50
0
Order By: Relevance
“…62 DNA fluorotags were also shown to be excellent FRET donors. 63 Conjugating a FRET acceptor (Cy5) at the end of the DNA oligomer resulted in efficient energy transfer from the two dyes with transfer efficiencies reaction over 70% in the 5′-EYYSS-Cy5−3′ sequence. 63 Further demonstrating the applicability of their DNA platform, Wang et al showed high-speed, multicolored tracking of various single and multicellular organisms.…”
Section: Molecular Interactions To Enhance Fluorescence Imagingmentioning
confidence: 99%
“…62 DNA fluorotags were also shown to be excellent FRET donors. 63 Conjugating a FRET acceptor (Cy5) at the end of the DNA oligomer resulted in efficient energy transfer from the two dyes with transfer efficiencies reaction over 70% in the 5′-EYYSS-Cy5−3′ sequence. 63 Further demonstrating the applicability of their DNA platform, Wang et al showed high-speed, multicolored tracking of various single and multicellular organisms.…”
Section: Molecular Interactions To Enhance Fluorescence Imagingmentioning
confidence: 99%
“…another Y or E) 45, 46 and it can also potentially function as a FRET donor for through-space energy transfer to an appropriate acceptor dye. 47, 48 If the styryl-pyran dye K was incorporated, the respective ODFs showed yellow to orange emission. Beads with red emission were found rather frequently, but the brightness of those beads was typically limited.…”
Section: Resultsmentioning
confidence: 99%
“…Since R 0 typically lies in the range 10-100 Å, FRET offers a convenient method for estimating distances in the molecular length-scale, especially in materials where the local environment changes drastically over only a few nm. Hence, FRET studies have been conducted in micelles [12], reverse micelles [13,14], vesicles [15], liposomes [16], ionic liquids [17,18], supramolecular assemblies [19], DNA [20], quantum dots and cyclodextrins [21], etc. Recently, there has been a spurt in energy transfer studies aimed for the development of novel white light emitting organogels like [22][23][24][25][26][27].…”
Section: = +mentioning
confidence: 99%